1988
DOI: 10.1111/j.1600-0528.1988.tb01781.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence study of oral leukoplakia in a selected population of 1000 patients from the Netherlands

Abstract: A survey of a special population, the outpatients of a Department of Oral Surgery of a Teaching Hospital in Amsterdam, revealed a comparatively low prevalence rate for oral leukoplakia of 14/1000 patients (1.4%). No difference was found in the age distribution compared with similar investigations elsewhere in the world. However, in contrast with previous findings, which show a significant difference between prevalences of leukoplakia for men and women, leukoplakia was equally distributed between both sexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 23 publications
5
22
0
1
Order By: Relevance
“…The susceptible age for leukoplakia lesions ranged from 40 to 70 years in a study from the Netherlands. In most age categories in this study, the number of women was larger than or equal to the number of men in the leukoplakia group (6). The present study showed a small female preponderance and largely affected elderly males, which is similar to the results of several other studies (4,5,7,20).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The susceptible age for leukoplakia lesions ranged from 40 to 70 years in a study from the Netherlands. In most age categories in this study, the number of women was larger than or equal to the number of men in the leukoplakia group (6). The present study showed a small female preponderance and largely affected elderly males, which is similar to the results of several other studies (4,5,7,20).…”
Section: Discussionsupporting
confidence: 81%
“…The major risk factors of oral leukoplakia (OL) are generally believed to correspond to those of oral squamous cell carcinoma (OSCC); tobacco, alcohol, chewing of areca nut and dietary factors (4). Several studies have shown that risk of OL is 4-6 times higher in smokers than in nonsmokers (5,6). It has also been suggested that OL lesions in smokers occur preferentially in particular locations in the oral cavity (7).…”
Section: Introductionmentioning
confidence: 99%
“…[421] This was, however, much higher than the 0.5% prevalence reported by Martínez Díaz-Canel and García-Pola Vallejo. [17] The relationship of leukoplakia with the tobacco habit is somewhat controversial.…”
Section: Discussionmentioning
confidence: 89%
“…This paper is the consensus outcome of a European workshop held in 1995. Epidemiology LP is a fairly common mucocutaneous disease. OLP affects from 0.1 to about 4% of individuals, depending on the population sampled (Bruszt, 1962;Bouquot and Gorlin, 86 Grit Rev Oral Biol Med (1998) 86 1986; Axell, 1987;Axell and Rundquist, 1987;Hogewind and Van der Waal, 1988;Axell et al, 1990;Salonen et cil, 1990;Ban6czy andRigo, 1991, Albrecht et al, 1992). OLP generally is a disease of the middle-aged and elderly (Silverman and Griffith, 1974), and the female-to-male ratio is about 2:1 ).…”
Section: Introductionmentioning
confidence: 99%